Immersion of betel leaf extract (Piper betle L.) against ectoparasite on gourami (Osphronemus gouramy) - Capriati, Erina; Mulyana; Farastuti, Eko Rini; Ananingtyas S. Darmarini (JURNAL MINA SAINS, 2025)
Ectoparasite infections frequently affect gourami fish during the seed (juvenile) phase. Immersion in piper betle extract can be a natural alternative treatment to reduce ectoparasitc infections by utulizing its bioactive compounds. This study aims to identify and analyze the prevalence and intensity of ectoparasite infecting juvenile gourami. The experimental design consisted of four treatments with three replications each. Treatment P1 (control), treatment P2 (piper betle extract at 150 mg/L), treatment P3 (piper betel extract at 200 mg/L), and treatment P4 (piper betle at 250 mg/L). The findings indicated that treatment P3 was the most effective in reducing the prevalence of Trichodina sp. (40%) and Dactylogyrus sp. (53%), and also achieved a survival rate of 90%. Treatment P4 was able to reduce the prevalence of Gyrodactylus sp. by 20%, as well as the Trichodina sp. (%), Gyrodactylus sp. (%), and Dactylogyrus sp. (%). However, the growth in length, absolute weight gain, and feed conversion ratio (FCR) were not significantly affected. The types of ectoparasite were found to infect juvenile gourami: Trichodina sp. (prevalence 40% and intensity 5 ind./fish), Gyrodactylus sp. (prevalence 20% and intensity 1 ind./fish), and Dactylogyrus sp. (prevalence 53% and intensity 2 ind./fish).